PENGARUH KEPEMIMPINAN, PENGAWASAN DAN HUKUMAN TERHADAP KEDISIPLINAN KERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN BIMA - Rahmat Kurniawan; Hermanto Hermanto; Agus Susanto (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Quality and competitive and reliable Human Resources (HR) in completing organizational tasks in order to realize a superior, clean and authoritative government system beginning with the enforcement of employee discipline. This research is an associative or causal research that examines the relationship between leadership, supervision and punishment variables as independent variables on work discipline as the dependent variable. The sample of this study was determined by calculation using the Slovin formula and the sampling technique using the Probability Sampling technique as many as 100 people as the research sample. Then the instrument for data collection is a questionnaire and before being used, the validity and reliability tests are carried out first. The data analysis technique is multiple linear regression analysis, namely the analysis of connecting more than two variables to determine the magnitude of the change from one variable to another variable or in other words a technique that aims to determine the contribution or influence of independent variables on the dependent variable. The results of the description analysis show that the leadership style belongs to the high/good category. Supervision of work is relatively high on average. Regarding punishment, the results showed that respondents rated professionalism in giving sanctions or punishments to employees who were not disciplined in their work as high and the basis for consideration was as good as possible. The average discipline is good/high. The results of multiple linear regression analysis that: (1) Leadership Style Has a Positive and Significant Effect on Employee Discipline; (2) Supervision Has a Positive and Significant Effect on Employee Discipline; (3) Punishment has a positive and significant impact on employee performance; and (4) Punishment is the dominant variable affecting the work discipline of the Regional Secretariat of Bima Regency. The Bima Regency Government, especially the Regent and Deputy Regent and officials within the Bima Regency, should be given strict sanctions for undisciplined employees while still prioritizing supervision and adjustment of their leadership style in order to improve employee work discipline.